Calcium Carbonate Addition Improves L-Methionine Biosynthesis by Metabolically Engineered Escherichia coli W3110-BL - Zhou, Hai-Yan; Wu, Wang-Jie; Xu, Yue-Ying; Zhou, Bin; Niu, Kun; Liu, Zhi-Qiang; Zheng, Yu-Guo (Frontiers in Bioengineering and Biotechnology, 2020)
L-Methionine (L-Met) is a sulfur-containing amino acid, which is one of the eight essential amino acids to human body. In this work, the fermentative production of L-Met with genetically engineered E. coli W3110-BL in a 5-L fermentor was enhanced through supplement of Ca2+ into the fermentation medium. With the addition of 30 g/L calcium carbonate (CaCO3), the titer of L-Met and yield against glucose reached 1.48 g/L and 0.09 mol/mol glucose, 57.45% higher than those of the control, respectively. The flux balance analysis (FBA) revealed that addition of CaCO3 strengthened the TCA cycle and increased the intracellular ATP concentration by 50.09%. The re-distribution of carbon, ATP, and cofactors flux may collaborate to improve L-Met biosynthesis with E. coli W3110-BL. The regulation of citrate synthase and oxidative phosphorylation pathway was proposed to be important for overproduction of L-Met. These foundations provide helpful reference in the following metabolic modification or fermentation control for further improvement of L-Met biosynthesis.